1999
DOI: 10.1175/1520-0485(1999)029<2266:ioieot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interbasin Exchange on the Atlantic Overturning Circulation

Abstract: The thermohaline exchange between the Atlantic and the Southern Ocean is analyzed, using a data set based on WOCE hydrographic data. It is shown that the salt and heat transports brought about by the South Atlantic subtropical gyre play an essential role in the Atlantic heat and salt budgets. It is found that on average the exported North Atlantic Deep Water (NADW) is fresher than the return flows (basically composed of thermocline and intermediate water), indicating that the overturning circulation (OC) expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(174 citation statements)
references
References 52 publications
(38 reference statements)
11
155
1
Order By: Relevance
“…Based on observational data, Weijer (38) found that the real AMOC exports freshwater from the Atlantic across 30°S (at a rate of Ϸ0.3 Sv); this indicates it may be bistable. An analysis of nine climate models in contrast found that all but one import freshwater via the AMOC (Weber et al in ref.…”
Section: Do Current Models Have Realistic Stability Properties?mentioning
confidence: 99%
“…Based on observational data, Weijer (38) found that the real AMOC exports freshwater from the Atlantic across 30°S (at a rate of Ϸ0.3 Sv); this indicates it may be bistable. An analysis of nine climate models in contrast found that all but one import freshwater via the AMOC (Weber et al in ref.…”
Section: Do Current Models Have Realistic Stability Properties?mentioning
confidence: 99%
“…The stability of the northern Agulhas Current has subsequently been studied and explained as being a consequence of a very steep continental slope (De Ruijter et al, 1999). The only place along its path where this does not hold is at the Natal Bight, a wider part of the shelf in a coastal offset north of Durban (see Fig.…”
Section: Northern Agulhas Currentmentioning
confidence: 99%
“…Based on a palaeo-climatological investigation it has even recently been demonstrated (Peeters et al, 2004) that this inter-ocean leakage has been particularly strong at the end of each of the last five glacial periods, but that it has never been absent entirely (Rau et al, 2002). Modelling studies by Weijer et al (1999Weijer et al ( , 2001Weijer et al ( , 2002 have in addition shown that a diminution in the exchange at the Agulhas retroflection leads inexorably to a slowing of the Atlantic Ocean's thermohaline overturning. The importance of this process of ring shedding at the Agulhas retroflection has thus been demonstrated during the past decade as have the mechanisms that control it.…”
Section: Agulhas Retroflectionmentioning
confidence: 99%
“…For example, in the POCM model (Stammer et al, 1994), the Agulhas has a realistic transport of 66 Sv and it indeed retroflects near 20 • E (De Ruijter et al, 1999). In these models, several other factors contribute to the retroflection, in particular vortex stretching due to the deformation of isopycnals .…”
Section: Introductionmentioning
confidence: 99%